Penerapan Teori Belajar Piaget untuk Meningkatkan Prestasi Belajar Siswa Kelas VII pada Mata Pelajaran PKN di SMP Negeri 1 Brang Rea Tahun Pelajaran 2020/2021 - Aenon Jariah (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2021)
The purpose of this classroom action research (PTK) was to determine the extent to which Piaget's learning theory was applied in improving student achievement in Civics. In this action research carried out in 3 cycles. From the results of the action taken is proven to increase student achievement by achieving ideal standards. From 59% in cycle 1, it can increase in cycle 2 to 84% and cycle 3 to 100%, and classically has reached completeness. The results of this action research indicate that the application of the PIAGET Learning Theory can improve the learning achievement of grade VII students with completeness reaching 100%, thus the PIAGET Learning Theory approach is effective in increasing student achievement at SMP Negeri 1 Brang Rea.